THE FOUNDATIONS OF THE MORAL IN ARTHUR SCHOPENHAUER'S WORK AND THE INTERPRETATION OF MAX HORKHEIMER - Rodrigues, Eli Vagner [UNESP] (Univ Federal Paraiba, 2017)
Schopenhauer asserts that a non-dogmatic ethic requires demonstrable laws derived from experience. In this sense, the foundation of an ethic must be an immanent metaphysics, which sustains in its possible experience its affirmations, and is therefore capable of giving once and for all a legitimate foundation to morality. The reasoning of Schopenhauerian morality therefore follows a very close argumentation of a scientific methodology. For Schopenhauer philosophy must approach more of a cosmology than of theology. Max Horkheimer inSchopenhauer's thinking in relation to science and religion highlights the fecundity of such a philosophical position and actualizes Schopenhauer's importance both for his formation and for a legitimate interpretation of modernity. We follow in this article both the fundamental aspects of Schopenhauer's moral foundation and aspects of Horkheimer's interpretation of the philosopher's work.
Keywords: pessimism; moral; compassion; ethics; science; religion